Environmental Ethics - DE933 - 202302 - Luqui Lagleyze De La Puente, Julio José (2023)
The readings for this course revolve around two clusters of questions. 1st, there are philosophical questions about the nature of value: What sorts of things have rights? What has value? What kinds of values are there? Does value presuppose the existence of valuers? Are there objective as well as subjective values? 2nd, there are practical questions about which social and legal arrangements help to preserve/promote environmental values. The first part of the course emphasizes the first while the second emphasizes the second, but the difference will be a matter of degree, since in theory and in practice it is hard (and probably unwise) to treat the two clusters as entirely separate